Circunferencia de cuello como indicador de sobrepeso y obesidad en escolares de la unidad educativa “Primero de Mayo”, Puyo-Ecuador. - Lema Lobato, Irene Jahaira (2023)
Introduction: The increasing prevalence of childhood overweight and obesity is alarming because of the repercussions it brings. Body mass index/age (BMI/age) is the most widely used indicator to identify nutritional status in the child population. Recently, there has been a growing interest in using neck circumference as a possible indicator of overweight. Objective: To determine the relationship between neck circumference and overweight/obesity in school children of the ¨Primero de Mayo¨ Educational Unit, Puyo. Methodology: Cross-sectional descriptive study, 220 schoolchildren between 6 and 10 years of age were evaluated. Anthropometric measurements of weight, height, and neck circumference were taken. The correlation between neck circumference and body mass index/age (BMI/Age) was determined using Spearman's correlation coefficient. The receiver operating curve (ROC) and area under the curve (AUC) were used to establish the cut-off point for neck circumference. Results: Neck circumference showed a significant moderate correlation with BMI/Age. The cut-off point for neck circumference to define overweight and obesity was calculated at 27.95 cm (AUC: 0.856, 95% CI: 0.804–0.909, sensitivity: 79.6%, specificity: 20.5%). Conclusion: A significant, moderate association was observed between neck circumference and BMI/Age in schoolchildren aged 6 to 10 years. Neck circumference is a simple, inexpensive, and non-invasive indicator that can be used in the detection of overweight and obesity.